The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1089/photob.2019.4712
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation in Oral Surgery: A Review

Abstract: Objective: This article presents a review of current data on the applications of photobiomodulation (PBM) in the field of oral and maxillofacial surgery (OMFS), to guide future research. Background data: Photobiomodulation therapy (PBMT) has been reported to be effective for various postoperative conditions, including pain relief, improvement of mastication, neurosensory recovery, and wound healing. There is a need for identifying the therapeutic irradiation windows for these conditions, based upon the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 73 publications
0
24
0
2
Order By: Relevance
“…Photobiomodulation (PBM) therapy is a term used for exposure of cells or tissues to low‐level laser light or light‐emitting diodes (LEDs), which is absorbed by specific photoreceptors in cells and may cause alteration at a molecular level inside cells without any heat generation leading to biological changes in cell metabolism and function (15). This noninvasive treatment also has medical and periodontal applications to provide pain relief, reduce inflammatory mediators and accelerate the wound healing process (16–18).…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation (PBM) therapy is a term used for exposure of cells or tissues to low‐level laser light or light‐emitting diodes (LEDs), which is absorbed by specific photoreceptors in cells and may cause alteration at a molecular level inside cells without any heat generation leading to biological changes in cell metabolism and function (15). This noninvasive treatment also has medical and periodontal applications to provide pain relief, reduce inflammatory mediators and accelerate the wound healing process (16–18).…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review of clinical trials revealed that the PBMT could have positive effects on pain after tooth extraction ( 27 ). In our analysis, PBMT showed a statistically significant effect immediately after surgery compared to the control group ( p <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…PBM therapy has been steadily gaining more attention as a safe, non-invasive treatment that could confer beneficial effects on multiple medical conditions, ranging from wound healing including the oral mucosa to deep tissue applications targeting muscle, adipose tissue, the nervous system, and the brain [23,[45][46][47][48][49]. However, some difficulties, such as the incomplete understanding of its mechanism(s) of action, and a lack of consensus in the field regarding optimal dosimetry and other treatment parameters, and organ-specific effectiveness still have to be resolved to optimize clinical applications.…”
Section: Discussionmentioning
confidence: 99%